Higher efficiency management of construction project for small scale contractor - Fum, S.C (University Malaysia Sarawak (UNIMAS), 1998)
This research will study the efficiency of the project management tools in apply to a small-scale contractor. This research involves case study (field test), where a small project near Kuching City was used.